2014
DOI: 10.1039/c4cc02812k
|View full text |Cite
|
Sign up to set email alerts
|

Emergent properties arising from the assembly of amphiphiles. Artificial vesicle membranes as reaction promoters and regulators

Abstract: This article deals with artificial vesicles and their membranes as reaction promoters and regulators. Among the various molecular assemblies which can form in an aqueous medium from amphiphilic molecules, vesicle systems are unique. Vesicles compartmentalize the aqueous solution in which they exist, independent on whether the vesicles are biological vesicles (existing in living systems) or whether they are artificial vesicles (formed in vitro from natural or synthetic amphiphiles). After the formation of artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 223 publications
0
106
0
Order By: Relevance
“…Besides providing a novel system where the transport and metabolism of glucose can be studied, we believe the broader implications are key for the development of future artificial cell mimics. 24 Moreover, the system has central implications for future strategies aimed at preventing or modulating the activity of glucose transport, which is of specific interest for cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…Besides providing a novel system where the transport and metabolism of glucose can be studied, we believe the broader implications are key for the development of future artificial cell mimics. 24 Moreover, the system has central implications for future strategies aimed at preventing or modulating the activity of glucose transport, which is of specific interest for cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…Although the component parts do not have to be those found in natural cells, artificial cells are typically made from biological molecules. For example, the compartment that houses the cellular mimic usually consists of phospholipid vesicles, even though compartments can be built from proteins, inorganic particles, block copolymers, polymers that form hydrogel structures, and submillimeter scale recesses within silicon chips [27][28][29][30][31]. Lipid bilayers that separate internal and external aqueous solutions are desirable, because such structures are better able to exchange molecules with the environment and can more easily accommodate components that confer molecular specificity, such as membrane proteins.…”
Section: Artificial Cellsmentioning
confidence: 99%
“…1 In this context, nanosized self-assembled architecture-based catalytic systems, such as bilayer vesicles, have been investigated. 2 Several research groups have reported that amphiphilic polymers and low-molecular weight amphiphiles containing a catalytically active site can self-assemble to form catalytically active selfassembled nanoarchitectures (micelles, vesicles, nanotubes, etc. ) that can be used to induce organic reactions in water.…”
Section: Introductionmentioning
confidence: 99%